"The Sound Exists Only in Your Own Body"—Sensory Approximation of Visual and Aural Impairment through Media Art Projects. Issue 1 (1st January 2021) - Lorenz, Jan
Abstract : This article is about art practice that aims at researching and recreating the condition of living with a particular sensory disability, and this through an interactive installation. The two artists whose work I investigate research the visual and aural experiences of themselves and others and attempt to recreate those experiences using computer-generated images and sounds: it is a process of sensory approximation. The audience interacting with these art installations, created in this process, are meant to experience—if for a moment—the condition of living with tinnitus and amblyopia, conditions that considerably affect one's sensorium. These multimodal attempts at transforming a person's bodily condition and sensorium into an intersubjective experience resonate with the methodological and epistemic concerns of sensory anthropology.